Biochemistry of smooth muscle contraction - Barany, Michael (Academic Press, 1996)
This valuable resource provides a systematic account of the biochemistry of smooth muscle contraction. As a comprehensive guide to this rapidly growing area of research, it covers the structure and characteristic properties of contractile and regulatory proteins, with special emphasis on their predicted function in the live muscle. Also included in this book are intermediate filament proteins, and desmin and vimentin, whose function in smooth muscle is unknown; and several enzymes involved in the phosphorylation-dephosphorylation of contractile and other proteins.